The impact of strategic planning in the universitys competitiveness according to NIAS - Hussein A.M.; Ahmed M.M.; Mahmoud Khu M.Y. (Richtmann Publishing Ltd, 2023)
Competition is one of the realities of the business environment, and despite this, the awareness of organizations (especially in developing countries) of the importance of dealing with it has not yet developed until in recent years. Developing countries are unable to follow these methods so that these competitive situations will be deeper and more powerful due to the clear interaction between not following the scientific method and adhering to random and improvisational methods, which is reflected in the capabilities of these organizations. The research deals with the impact of strategic planning (external orientation, internal orientation, functional coverage, and resources provided for strategic planning) in the university's competitiveness (the strategy of the educational institution, Governance and management, Financial and material resources, Faculty members, Students, Scientific research, Community service, Curricula), as an expression of a vision of the role of strategic planning in achieving effective adaptation to competitive situations and improving the university's competitiveness, to establish a reality in the minds of the leaders responsible for the planning process that working in traditional contexts in light of the changes and accumulating problems of the Iraqi environment leads to results that are not effective concerning the size of the problems. Hence, the research problem arises by raising a major question which is: What is the impact of strategic planning on the competitiveness of Iraqi universities according to the national institutional accreditation standards of the Iraqi Ministry of Higher Education and Scientific Research? To achieve the goal of the research and answer its questions, the research applied to a sample of (158) individuals at the University of Technology and the research adopted the questionnaire to collect the data that were processed and analyzed using several statistical methods. The research reached several results, including the researched university has employed strategic planning with all its indicators to improve its competitiveness. the most important recommendations were the necessity for the university to employ more strategic planning to improve the university's competitiveness. 2021 Hussein et al.